2011
DOI: 10.1089/ten.tea.2011.0229
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Intervertebral Disc Repair Using Allogeneic Juvenile Articular Chondrocytes or Mesenchymal Stem Cells

Abstract: Tissue engineering strategies for intervertebral disc repair have focused on the use of autologous disc-derived chondrocytes. Difficulties with graft procurement, harvest site morbidity, and functionality, however, may limit the utility of this cell source. We used an in vivo porcine model to investigate allogeneic non-disc-derived chondrocytes and allogeneic mesenchymal stem cells (MSCs) for disc repair. After denucleation, lumbar discs were injected with either fibrin carrier alone, allogeneic juvenile chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 56 publications
0
126
0
2
Order By: Relevance
“…Multiple preclinical animal studies have demonstrated the efficacy of intradiscally injected mesenchymal stem cells (MSCs) to induce disc regeneration. 1,2,16,18,20,21,25,[31][32][33][34]38,39,49,53,56,60,[64][65][66]69,73,83,87,90 Allogeneic mesenchymal progenitor cells (MPCs) are the earliest uncommitted clonogenic population of bone marrow stromal cells and have also successfully repaired the extracellular matrix following their injection into degenerative ovine discs. 25 Moreover, when ovine MPCs combined with the chondrogenic agent pentosan polysulfate (PPS) were embedded in a gelatin sponge and placed in a biodegradable cage that was implanted into the interbody space of ovine cervical spines, the cage became filled with a predominately cartilaginous matrix.…”
mentioning
confidence: 99%
“…Multiple preclinical animal studies have demonstrated the efficacy of intradiscally injected mesenchymal stem cells (MSCs) to induce disc regeneration. 1,2,16,18,20,21,25,[31][32][33][34]38,39,49,53,56,60,[64][65][66]69,73,83,87,90 Allogeneic mesenchymal progenitor cells (MPCs) are the earliest uncommitted clonogenic population of bone marrow stromal cells and have also successfully repaired the extracellular matrix following their injection into degenerative ovine discs. 25 Moreover, when ovine MPCs combined with the chondrogenic agent pentosan polysulfate (PPS) were embedded in a gelatin sponge and placed in a biodegradable cage that was implanted into the interbody space of ovine cervical spines, the cage became filled with a predominately cartilaginous matrix.…”
mentioning
confidence: 99%
“…Chondrocytes proved to be more effective in restoring disc height and matrix production than MSCs or cell free controls (Acosta et al, 2011).…”
Section: Fibrinmentioning
confidence: 98%
“…Cloyd et al, 2007;Gruber et al, 2006;Gupta et al, 2014;Hunt and Grover, 2010;Lazebnik et al, 2011;Nerurkar et al, 2010;Tilwani et al, 2012;Zhang et al, 2012 Fibrin Human plasma Surgical sealant Used as a singular or hybrid scaffold for NP and AF in vitro and in vivo testing. Acosta et al, 2011;Ahmed et al, 2008;Colombini et al, 2014;Diederichs et al, 2012;Eyrich et al, 2007;Hegewald et al, 2010;Ho et al, 2010;Likhitpanichkul et al, 2014;Ma et al, 2012;Park et al, 2011b;Pirvu et al, 2015;Schek et al, 2011;Stern et al, 2000;Stern et al, 2004;Sung et al, 1999;…”
Section: Culture Mediamentioning
confidence: 99%
“…Despite showing improvements in symptoms and functionality following lumbar discectomy for symptomatic disc herniation, concerns remain with the use of alternative non-disc chondrocytes or mesenchymal stem cells (MSCs) (Acosta et al, 2011). In the case of NuQuÂŽ, issues still remain with supply and demand reconciliation using cadaveric juvenile chondrocytes and potential immunogenic reactions and rejection (Adkisson et al, 2010) which have not been elucidated for the disc microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advancements in the development of commercial ventures such as ADCT and NuQuÂŽ, identification of an alternative cell source for robust regeneration is crucial to further advancement. While investigative trials continue for immunoselected adipose derived precursor cells (Mesoblast Ltd., Australia), additional growth factors (GFs) such as transforming growth factor-beta 3 (TGF-β3) to induce and maintain chondrogenic differentiation (Acosta et al, 2011;Bobick et al, 2009) makes the use of adult MSCs challenging. Interestingly, within the degenerated human IVD, local progenitor cell populations have been identified previously (Risbud et al, 2007) and shown to exhibit slow cell proliferation kinetics in both annulus fibrosis and nucleus pulposus (Henriksson et al, 2009a) tissues.…”
Section: Introductionmentioning
confidence: 99%